2017
DOI: 10.1002/14651858.cd010285.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic therapy for pelvic inflammatory disease

Abstract: Antibiotic therapy for pelvic inflammatory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 108 publications
2
36
0
3
Order By: Relevance
“…Western medicine uses antibiotics to effectively control the symptoms (Jaiyeoba et al, 2011;Bugg and Taira, 2016). However, no conclusive evidence indicated that antibiotic treatment for the pelvic inflammatory disease was safer or more effective than other methods (Savaris et al, 2017). Endometriosis is a common inflammatory disease often accompanied by pelvic pain and infertility.…”
Section: Effects On Gynecological Diseasesmentioning
confidence: 99%
“…Western medicine uses antibiotics to effectively control the symptoms (Jaiyeoba et al, 2011;Bugg and Taira, 2016). However, no conclusive evidence indicated that antibiotic treatment for the pelvic inflammatory disease was safer or more effective than other methods (Savaris et al, 2017). Endometriosis is a common inflammatory disease often accompanied by pelvic pain and infertility.…”
Section: Effects On Gynecological Diseasesmentioning
confidence: 99%
“…Previous studies have reported similar data and recommend that PID management should be based on clinical features 9,25 . In the present study, hospitalization was decided according to clinical criteria 1,14,15,17 and all patients were treated with broad-spectrum antibiotic regimens to cover likely pathogens, including CT and NG, irrespectively of the results 1,4,18 . Likewise, the economic analysis showed no cost differences between CT/NG-positive and negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were classified as having mild-to-moderate or severe PID according to clinical symptoms and signs and complementary test results 3,17,18 . Severe PID was defined in this study as the presence of severe symptoms or signs and/or the presence of tubo-ovarian abscess at imaging tests 3,17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic inflammatory disease (PID) is an infectious polymicrobial disorder of the upper genital tract that affects around 4-12% of young women worldwide [1]. This clinical entity can be attributed to a variety of bacteria.…”
Section: Introductionmentioning
confidence: 99%